2022
DOI: 10.3390/healthcare10122423
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden among Caregivers of Patients with Mental Illness: A Systematic Review and Meta-Analysis

Abstract: Due to the increasing importance of caregivers in the treatment outcomes of patients with mental illness, this study aimed to systematically review studies investigating the former’s caregiver burden and determine its prevalence. An open search, without filters, was conducted. Articles were selected from Medline, Scopus, and PubMed from inception to 30 April 2022 using the PRISMA protocol. Subgroup analyses examined the between-group differences by study setting, measurements used, and disorder type. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 103 publications
2
21
0
1
Order By: Relevance
“…Schizophrenia is a disease that affects the brain and can be seen as the reason for publishing the most articles from the field of psychiatry, as it includes situations and behaviors that are out of the ordinary. Cham et al (2022) included 39 studies in the systematic review, and according to a meta-analysis of 26 of them, the perceived care burden of individuals who care for individuals with mental illness constituted 31.67% of the general population. In the same study, psychosis symptoms such as disordered thoughts, hallucinations, and delusions, conditions that require constant monitoring such as maintaining the patient's personal hygiene and care and taking medication, the need for constant care, and the social exclusion they experience were found to be the reason why caregivers of individuals with schizophrenia felt a higher care burden (Cham et al, 2022).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia is a disease that affects the brain and can be seen as the reason for publishing the most articles from the field of psychiatry, as it includes situations and behaviors that are out of the ordinary. Cham et al (2022) included 39 studies in the systematic review, and according to a meta-analysis of 26 of them, the perceived care burden of individuals who care for individuals with mental illness constituted 31.67% of the general population. In the same study, psychosis symptoms such as disordered thoughts, hallucinations, and delusions, conditions that require constant monitoring such as maintaining the patient's personal hygiene and care and taking medication, the need for constant care, and the social exclusion they experience were found to be the reason why caregivers of individuals with schizophrenia felt a higher care burden (Cham et al, 2022).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Cham et al (2022) included 39 studies in the systematic review, and according to a meta-analysis of 26 of them, the perceived care burden of individuals who care for individuals with mental illness constituted 31.67% of the general population. In the same study, psychosis symptoms such as disordered thoughts, hallucinations, and delusions, conditions that require constant monitoring such as maintaining the patient's personal hygiene and care and taking medication, the need for constant care, and the social exclusion they experience were found to be the reason why caregivers of individuals with schizophrenia felt a higher care burden (Cham et al, 2022). In this study, it was seen that the most important keywords were "schizophrenia", "caregivers", Volume/Cilt:5, Issue/Sayı:3, 2023 Humanistic Perspective 1111 Şanlı, Karatağ and Çiçek Bibliometric Analysis of Academic Publications for Caregivers of Individuals with Schizophrenia "caregiver", "quality of life", and "burden".…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…The key tenets of the intervention in psychosis are the balance between the need for and the impact of care, the particular difficulties of pressure to recover and of coping with hard to understand experiences in the context of insight-related and other communication difficulties (Kuipers et al, 2002). While there may be similarities across serious mental health presentations in terms of caregiver appraisals, impact on caregivers, caregiver coping and communication, and impact of this on the condition (Cham et al, 2022), evidence for the requirement for care in order to improve mortality, morbidity and quality of life outcomes, and the need to support without intrusion, is lacking for conditions other than psychosis. Family and caregiver recommendations for depression and personality presentations highlight different primary processes, and there is a dearth of evidence regarding any adjustments required for the presence of psychosis symptoms (NICE, 2009(NICE, , 2022.…”
Section: Framing the Conditionmentioning
confidence: 99%
“…Guidelines do not usually differentiate particular psychosis presentations: all families where there is psychosis are considered eligible for FIp (NICE, 2014), and psychoeducation accordingly covers diagnostic uncertainty and complexity (Health Education England, 2020; Roth & Pilling, 2013). Evaluation is lacking regarding adaptations to the intervention to best address affective, interpersonal, neurodevelopmental and substance use comorbidity: each of these may impact the task of adjustment for caregivers, particularly comorbidity with organic disorders in older adults (Bayes et al, 2019; Cham et al, 2022; Dobri et al, 2022; Karambelas et al, 2022; Reynolds et al, 2022). It is also unclear whether the same approach ought to be recommended for psychosis symptoms occurring secondarily to a mood condition, or complex emotional and interpersonal difficulties (NICE, 2009, 2022).…”
Section: Why the Implementation Gap?mentioning
confidence: 99%
“…2 In addition, a number of studies has shown that caregivers' mental state is negatively affected. 3 Lately, the number of published studies on family distress and the negative experience of relatives caring for ED patients has risen. [4][5][6][7] According to these studies caregivers of ED patients demonstrate poor quality of life, depression, anxiety, loss of behavioral or emotional control, and low psychological well-being.…”
Section: Introductionmentioning
confidence: 99%